license for professionalizing education in Egypt as a way for professionalizing teacher's job. - Howida Eletrebi (International Journal of Instructional Technology and Educational Studies)
The issue of preparing teachers has been a forcing concern for a lot of educators in Egypt especially at the age of rapid technological changes. So, certain rules should be issued to guarantee choosing the best teachers; the thing which cannot be achieved without professionalizing education by issuing licenses for working as teachers. The license of professionalizing the job of teachers is considered an acknowledgement of the teacher's ability to teach. In addition, this license encourages teachers to develop themselves and upgrade their imaginative thinking for a long time. There must be an official department to issue this licence according to regulations and criteria corresponding with the necessary regulations for doing the teaching effectively and efficiently.